Multiply the First terms, then the Outer terms, the Inner terms and lastly, the Last terms (which all adds up to a handy dandy acronym: FOIL).
(2a - 6)(3a + 5)
multiply the first: 2a x 3a = 6a^2
multiply the outer: 2a x 5 = 10a
multiply the inner: -6 x 3a = -18a
multiply the last: -6 x 5 = -30
Now smash them all together
6a^2 + 10a - 18a - 30
And then simplify
6a^2 - 8a - 30
2007-04-07 07:20:44
·
answer #1
·
answered by RyanGoff 2
·
1⤊
0⤋
FOIL (first) (outside) (inside) (last)
2a times 3a=6a squared
2a times 5=10a
-6 times 3a=-18a
-6 times 5=-30
now combine like terms and solve
apples go with apples
6a SQUARED-8a-30
because it's a negative 18
so the answer is
6a SQUARED-8a-30
UHHH I THINK...
2007-04-07 07:23:21
·
answer #2
·
answered by Lucky 2
·
0⤊
0⤋
use foil method f=first o=outer i=inner l=last; 2a x 3a=6a squared; 5 x 2a=10a; -6 x 3a=-18a; -6 x 5=-30; -18a combines with 10a to form -8a; final answer is 6asquared -8a -30
2007-04-07 07:21:15
·
answer #3
·
answered by Dave R 1
·
0⤊
0⤋
Just multiply out, term by term, and then collect like terms:
6a^2 + 10a -18a - 30 = 6a^2 - 8a - 30 = 2(3a^2-4a-15)
2007-04-07 07:17:07
·
answer #4
·
answered by kellenraid 6
·
0⤊
0⤋
to unravel this regularly happening change in "x" for 3a - 4 Now your equation appears like this: 2x^2 = 5x-2 2x^2 - 5x + 2 = 0 (2x - a million) (x - 2) = 0 x = 2, a million/2 now go back to come across a: 3a - 4 = 2 ........ 3a - 4 = a million/2 3a = 6 ............. 3a = 4.5 a = 2 ............... a = a million.5
2016-11-27 01:29:50
·
answer #5
·
answered by hillyard 4
·
0⤊
0⤋
FOIL
(2a - 6)(3a + 5)=
6a² - 18a + 10a - 30 =
6a² - 8a - 30
- - - - - - -s-
2007-04-07 08:20:15
·
answer #6
·
answered by SAMUEL D 7
·
0⤊
0⤋
you need to multiply every term in the first binomial by every term in the second, and add all the results.
6a^2+10a-18a-30
and now to add like terms:
6a^2-8a-30
2007-04-07 07:17:49
·
answer #7
·
answered by MLBfreek35 5
·
0⤊
0⤋
You can do it, this is not hard. Let me help.
FOIL! (First, Outer, Inner, Last)
F = 2a x 3a
O = 2a x 5
I = -6 x 3a
L = -6 x 5
when you are done, combine like terms
You can do it, this is not hard. Let me help.
2007-04-07 07:21:19
·
answer #8
·
answered by SheTigger2 4
·
0⤊
0⤋
Believe answer is: 6asquared -8a-30
2007-04-07 07:16:44
·
answer #9
·
answered by RAN 2
·
0⤊
0⤋
= 6a^2 -8a -30
2007-04-07 07:16:44
·
answer #10
·
answered by tuoidabuon 2
·
0⤊
0⤋